The Effect of the SQ3R Strategy Assisted by Interactive Multimedia on Grade V Student’s Reading Comprehension - Yona Rahmawati; Andarini Permata Cahyaningtyas (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study examined the effect of the SQ3R strategy assisted by interactive multimedia on fifth-grade students’ reading comprehension and compared it with conventional learning. Using a quantitative quasi-experimental nonequivalent control group design, the study involved Grade V students of SD Negeri 1 Cening, divided into experimental and control classes. The instrument was a short-story reading comprehension test administered as pretest and posttest. Data were analyzed using prerequisite tests, Paired Sample t-test, Independent Sample t-test, and N-Gain analysis. Results showed a significant effect in the experimental class (Sig. two-tailed <0.001; mean difference = -29.350). The independent test also indicated a significant difference between groups (t = -2.741; Sig. = 0.009; mean difference = -11.191). The N-Gain score of 0.47 was moderate, suggesting that the SQ3R strategy supported by interactive multimedia is effective for active and meaningful reading comprehension learning in elementary schools and can serve as an innovative alternative for literacy instruction in primary classrooms effectively.